The Continuous Monitoring of the Health of Composite Structure - T. P. Masango; O. Philander; V. Msomi (Journal of Engineering)
Currently nondestructive testing techniques for composite aircraft structures are disadvantaged when compared to instant structural health monitoring (SHM) systems that monitor the structure while being in-service and give real-time data. This paper reports on the use of Polyvinylidene Fluoride (PVDF) sensors in sensing (or monitoring) and locating the defect of a flexible composite structure. The samples used for the tests were manufactured through the use of vacuum infusion process. The three-point bending test was performed to determine the material properties. The vertical sample deflection was measured through the use of vertical height Vernier. It should be noted that the samples were analyzed as cantilever beam due to limited availability of test equipment. The sample health was monitored through the use of PVDF sensor. The sensor data was logged and recorded through the use of Fluke-View scopemeter. The 50 g mass pieces were used as a mode of subjecting the structure to the vertical load. The experiment was performed on samples with defects (drilled 3 mm hole) sample and no-defected sample. The deflection and output voltage from the PVDF sensor of all the samples were comparatively studied.